Survey on prevalence and risk factors on HIV-1 among pregnant women in North-Rift, Kenya: a hospital based cross-sectional study conducted between 2005 and 2006 - Ng'ang'a Zipporah; Mpoke Solomon; Kiptoo Michael; Mueke Jones; Okoth Fredrick; Songok Elijah (BMC, 2009)
Abstract Background The HIV/AIDS epidemic in Kenya is a major public-health problem. Estimating the prevalence of HIV in pregnant women provides essential information for an effective implementation of HIV/AIDS control measures and monitoring of HIV spread within a country. The objective of this study was to determine the prevalence of HIV infection, risk factors for HIV/AIDS and immunologic (lymphocyte profile) characteristics among pregnant women attending antenatal clinics in three district hospitals in North-Rift, Kenya. Methods Blood samples were collected from pregnant women attending antenatal clinics in three district hospitals (Kitale, Kapsabet and Nandi Hills) after informed consent and pre-test counseling. The samples were tested for HIV antibodies as per the guidelines laid down by Ministry of Health, Kenya. A structured pretested questionnaire was used to obtain demographic data. Lymphocyte subset counts were quantified by standard flow cytometry. Results Of the 4638 pregnant women tested, 309 (6.7%) were HIV seropositive. The majority (85.1%) of the antenatal attendees did not know their HIV status prior to visiting the clinic for antenatal care. The highest proportion of HIV infected women was in the age group 21-25 years (35.5%). The 31-35 age group had the highest (8.5%) HIV prevalence, while women aged more than 35 years had the lowest (2.5%). Women in a polygamous relationship were significantly more likely to be HIV infected as compared to those in a monogamous relationship (p = 0.000). The highest HIV prevalence (6.3%) was recorded among antenatal attendees who had attended secondary schools followed by those with primary and tertiary level of education (6% and 5% respectively). However, there was no significant relationship between HIV seropositivity and the level of education (p = 0.653 and p = 0.469 for secondary and tertiary respectively). The mean CD4 count was 466 cells/mm3 (9-2000 cells/mm3). Those that had less than 200 cells/mm3 accounted for 14% and only nine were on antiretroviral therapy. Conclusion Seroprevalence of HIV was found to be consistent with the reports from the national HIV sentinel surveys. Enumeration of T-lymphocyte (CD4/8) should be carried out routinely in the antenatal clinics for proper timing of initiation of antiretroviral therapy among HIV infected pregnant women.